Efeitos do ciclamato de sódio sobre o testículo fetal de ratos: estudo morfométrico - Santos, Vera Lúcia Fugita dos (2006)
Objective: To evaluate the effects of sodium cyclamate on fetal growth and on testicular cells of rat fetuses treated during embryogenesis. Method: From the tenth to the thirteenth day of pregnancy, 50 mg/Kg sodium cyclamate was administered via intraperitoneally in rats participating in the Treated Group. An equal volume of distilled water was similarly administered to rats of a Control Group. The fetuses were removed on the twentieth day by laparotomy, when 5 fetuses were randomly selected from the both Treated and Control Groups. Using karyometry, the nuclear parameters of the testicular cells were evaluated in respect to gonocytes, Sertoli cells and Leydig cells. Results: The mean fetal and placental weights of the animals from the Treated Group were lower than those of the Control Group, with a similar result seen in respect to the length of the umbilical cord. No changes were seen in the nuclei of the gonocytes. In relation to the Sertoli cells, differences were observed in the lowest diameter, mean diameter, volume, area, volume:area ratio and perimeter. No nuclear alterations were identified in the Leydig cells. Conclusions: This study identified alterations in fetal growth and in the testicular cells of rat fetuses caused by the administration of sodium cyclamate during the gestational period.